THE DEVELOPMENT OF THE SCIENCE PROGRAM IN TEACHER EDUCATION AT MADISON COLLEGE. - Shawver, Murl C. (Science Education, 1954)
The article discusses the development of the science program in teacher education at Madison College in Virginia. Madison has granted degrees since 1919. The program at Madison now provides seven divisions or fields of concentration in which students may elect to direct their efforts in planning their college work. Courses in the sciences were a part of the first offerings of Madison College when it was founded as the Normal and Industrial School for Women. It is expected that a few students who come to Madison might be able to demonstrate a competence in certain areas of the general education program. A six semester-hour professionalized-content course in the physical sciences is now required of those student preparing to be elementary teachers.